2022
DOI: 10.3390/ijerph19074281
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Sulfonamide Resistance Genes in Fishery Reclamation Mining Subsidence Area by Zeolite

Abstract: A majority of subsidence lakes were reclaimed as fish ponds, but the widespread use of antibiotics has caused the pollution of antibiotic resistance genes (ARGs). This paper uses zeolite as a filter material to construct a horizontal submersible wastewater treatment device and explores its effect on the removal of conventional pollutants and sulfonamide ARGs in wastewater. The results showed that the removal of total nitrogen and ammonia nitrogen by the zeolite filter media were 59.0% and 63.8%, respectively, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Overall, the high removal of all pollutants obtained could be attributed to the high HRT (14 days), as many studies reported that the residence time of treatment significantly impacts the removal of pollutants ( Yuan et al, 2022 ). This study makes a valuable contribution to the application of vertical subsurface flow CWs with gravel, LECA and sand, planted with S. erectum as a decentralized wastewater treatment technology to treat LFD with metals and antibiotics for water reuse purposes.…”
Section: Resultsmentioning
confidence: 92%
“…Overall, the high removal of all pollutants obtained could be attributed to the high HRT (14 days), as many studies reported that the residence time of treatment significantly impacts the removal of pollutants ( Yuan et al, 2022 ). This study makes a valuable contribution to the application of vertical subsurface flow CWs with gravel, LECA and sand, planted with S. erectum as a decentralized wastewater treatment technology to treat LFD with metals and antibiotics for water reuse purposes.…”
Section: Resultsmentioning
confidence: 92%
“…Moreover, these aquaponic system designs can be used in a denitrification process of water due to water filtration in the hydroponic systems [146]. In difference, open aquaponics are capable too to optimize the water usage of food production [38], but this system design can still cause soil pollution if there is an uncontrolled application of concentrates nutrients of aquaculture wastewater [38,160].…”
Section: Optimization Of Groundwater Employment In Aquaponic Food Pro...mentioning
confidence: 99%
“…Moreover, these aquaponic system designs can be used in a denitrification process for water due to water filtration in hydroponic systems [145]. In contrast, open aquaponics are capable too of optimizing water usage in food production [38], but this system design can still cause soil pollution if there is an uncontrolled application of concentrated nutrients in aquaculture wastewater [38,159].…”
Section: Optimization Of Groundwater Employment In Aquaponic Food Pro...mentioning
confidence: 99%